2015
DOI: 10.14737/journal.aavs/2015/3.6.354.361
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dietary Energy Level, Silage Butyric Acid and Body Condition Score with Subclinical Ketosis Incidence in Dairy Cows

Abstract: | Subclinical ketosis is one of the most prevalent metabolic disorders that usually occurs in cows during the first weeks of lactation. This study investigated the relationship between energy level, body condition score and silage butyric acid with incidence of subclinical ketosis (SCK) in dairy cows during the first month of postpartum. Fifty healthy pregnant Holstein cows from 10 commercial dairy farms were studied. Whole blood β-hydroxybutyrate (BHBA) concentration equal or more than 1,400 µmol/L, at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…This was in agreement with Gillund et al (2001) and Bewley and Schutz (2008). Samiei et al (2015) observed a reduction of more than 0.5 units on BCS of animals during the first month of lactation and reported that BCS of animals on 3 rd , 14 th and 28 th day postpartum exhibited a strong correlation with body condition score at calving.…”
Section: Risk Factors Associated With Occurrence Of Scksupporting
confidence: 89%
“…This was in agreement with Gillund et al (2001) and Bewley and Schutz (2008). Samiei et al (2015) observed a reduction of more than 0.5 units on BCS of animals during the first month of lactation and reported that BCS of animals on 3 rd , 14 th and 28 th day postpartum exhibited a strong correlation with body condition score at calving.…”
Section: Risk Factors Associated With Occurrence Of Scksupporting
confidence: 89%
“…Animal studies on the ketogenic potential of butyrate are mixed. For example, silage butyrate content has been shown to provide no significant effect on subclinical ketosis in dairy cows ( Samiei et al, 2015 ), however, sub-clinical ketosis is higher in those receiving silage higher in butyrate content ( Vicente et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Animal studies on the ketogenic potential of butyrate are mixed. For example, silage butyrate content has been shown to provide no significant effect on subclinical ketosis in dairy cows, 62 however, sub-clinical ketosis is higher in those receiving silage higher in butyrate content. 63 In a recent study in humans, the effect of L-leucine, octanoyl-monoacylglycerol (O-MAG), a monoglyceride consisting of an 8-carbon fatty acid, L-carnitine, and butyric acid on acetoacetate and BOHB were studied.…”
Section: Butyric Acidmentioning
confidence: 99%